An integrated structure and control design of a coaxis planar parallel manipulator for pick-and-place applications based on elastic potential energy. (22nd October 2021) - Liao, Bin; Gao, Xingyu; Lou, Yunjiang
During high-speed pick-and-place operations, elastic deformations are quite apparent if the mass of the manipulator is low. These irregular deformations are accompanied by vibrations, then errors. Since elastic potential energy reflects elastic deformation, the vibration of the whole manipulator can be controlled well when the elastic potential energy is decreased. In this article, to design manipulators with flexible links for pick-and-place operations, an integrated structure and control design framework is proposed. The dynamic model of a coaxis planar parallel manipulator is obtained by the finite element method, an effective method. A proportional–derivative controller is utilized for this industrial application. Simultaneously, the optimal structural and control parameters are derived by minimizing the elastic potential energy via integrated design, in which actuated systems and accuracies are regarded as constraints. Finally, simulations show that the performance of the parallel manipulator is improved by this design methodology.